Keluarga Kristiani di Sumba dalam Himpitan Tradisi: Menafsirkan Tradisi Budaya Menuju Kearifan Lokal - Panda, Herman P. (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2016)
he obstructions to the families’ welfare in Sumba are the local tradition of dowry in marriage affair and other traditional parties which cause the economical burdens of the families. Christian families are also still impeded by such traditions. Actually, the customs of dowry and traditional parties have been so modified and even manipulated as such in the course of history, so that they become obstacle to the families’ welfare. Therefore, it is necessary to turn back to the substance of the local custom by omitting these deviations. By doing so, one can determine which is the real local wisdom that has to be maintained.